Evaluation of market competitiveness of SMEs in the Malaysian food processing industry - Shamsudin, Mad Nasir; Yodfiatfinda,; Mohamed, Zainal Abidin; Yusop, Zulkornain; Radam, Alias (Federal Agricultural Marketing Authority, 2011)
This study aims to evaluate the market competitiveness of Small and Medium Enterprises (SMEs) in the Malaysian Food Processing Industry (FPI) in terms of technical efficiency and productivity growth. A non-parametric approach using Data Envelopment Analysis (DEA) was employed for the five-digit data of 35 sub-industries in the Malaysian FPI. The findings suggest that Technical Efficiency (TE) was 0.756 during the period of 2000-2006, indicating that SMEs in the Malaysian food industry were able to expand their output by 24.4 percent while using the same level of inputs. Total Factor Productivity (TFP) growth was negative 1.3 percent. Processing and preserving poultry and poultry products was the sub-industry with the highest productivity growth, while manufacturing of tea had the lowest. Research and development (R&D), training and public infrastructure were determinants that positively affected the TFP growth. For technical efficiency, public infrastructure, foreign direct investment and foreign ownership were the determinants.